2012
DOI: 10.1063/1.4756693
|View full text |Cite
|
Sign up to set email alerts
|

Electron transport properties of carbon nanotube–graphene contacts

Abstract: The properties of carbon nanotube-graphene junctions are investigated with first-principles electronic structure and electron transport calculations. Contact properties are found to be key factors in determining the performance of nanotube based electronic devices. In a typical single-walled carbon nanotube-metal junction, there is a p-type Schottky barrier of up to ∼0.4 eV which depends on the nanotube diameter. Calculations of the Schottky barrier height in carbon nanotube-graphene contacts indicate that low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
35
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 35 publications
2
35
0
Order By: Relevance
“…Owing to the similarity in electronic properties, it was found that no obvious Schottky barrier exists at metallic SWNT/graphene junction, which means that graphene is a good contact material for metallic CNTs while there is a Schottky barrier between semiconducting SWNT and graphene, resulting in a typical rectification properties and directionally field‐effect behavior . Such transport properties were also revealed by theoretical studies . Very recently, it was reported that the alignment of SWNTs on graphite surface is chirality dependent.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Owing to the similarity in electronic properties, it was found that no obvious Schottky barrier exists at metallic SWNT/graphene junction, which means that graphene is a good contact material for metallic CNTs while there is a Schottky barrier between semiconducting SWNT and graphene, resulting in a typical rectification properties and directionally field‐effect behavior . Such transport properties were also revealed by theoretical studies . Very recently, it was reported that the alignment of SWNTs on graphite surface is chirality dependent.…”
Section: Introductionmentioning
confidence: 96%
“…Besides the CNT‐graphene bulk hybrids, individual SWNT‐graphene systems are also of great importance. Very careful measurements on the transport behavior of SWNT‐graphene junctions show some interesting results . Owing to the similarity in electronic properties, it was found that no obvious Schottky barrier exists at metallic SWNT/graphene junction, which means that graphene is a good contact material for metallic CNTs while there is a Schottky barrier between semiconducting SWNT and graphene, resulting in a typical rectification properties and directionally field‐effect behavior .…”
Section: Introductionmentioning
confidence: 99%
“…For example, high conductance and low contact resistance were observed in CNT-CNT junctions [65,[72][73][74]. If only recently theoretical work succeeded to model the transport across a CNT-graphene junction [75] the first experiments in this field were performed more than a decade ago: conducting atomic force microscopy on CNT-graphite (i.e. highly oriented pyrolitic graphite) junctions were investigated using conductive atomic force microscopy in [76].…”
Section: Introductionmentioning
confidence: 99%
“…In the last years, many studies have addressed the contact effect in graphene-based transistors 35,36 . It has been shown that the contact type and contact position may determine the I ON to I OFF ratio 37,38 and contact resistance [39][40][41] . The height of the Schottky barrier at CNT-graphene contacts can be about one order lower than that at Pd-graphene contacts 38 .…”
Section: Introductionmentioning
confidence: 99%